Redox Control of Antioxidant and Antihepatotoxic Activities ofCassia surattensisSeed Extract against Paracetamol Intoxication in Mice: In Vitro and In Vivo Studies of Herbal Green Antioxidant - Uthaya Kumar, U.S.; Chen, Y.; Kanwar, J.R.; Sasidharan, S. (Hindawi Publishing Corporation, 2016)
The therapeutic potential of Cassia surattensis in reducing free radical-induced oxidative stress and inflammation particularly in hepatic diseases was evaluated in this study. The polyphenol rich C. surattensis seed extract showed good in vitro antioxidant. C. surattensis seed extract contained total phenolic content of 100.99 mg GAE/g dry weight and there was a positive correlation () between total phenolic content and the antioxidant activities of the seed extract. C. surattensis seed extract significantly () reduced the elevated levels of serum liver enzymes (ALT, AST, and ALP) and relative liver weight in paracetamol-induced liver hepatotoxicity in mice. Moreover, the extract significantly () enhanced the antioxidant enzymes and glutathione (GSH) contents in the liver tissues, which led to decrease of malondialdehyde (MDA) level. The histopathological examination showed the liver protective effect of C. surattensis seed extract against paracetamol-induced histoarchitectural alterations by maximum recovery in the histoarchitecture of the liver tissue. Furthermore, histopathological observations correspondingly supported the biochemical assay outcome, that is, the significant reduction in elevated levels of serum liver enzymes. In conclusion, C. surattensis seed extract enhanced the in vivo antioxidant status and showed antihepatotoxic activities, which is probably due to the presence of phenolic compounds.